Balinese Way of Governing Water: A Social Survey on Water Governance - IGNGA Pradipta; Herdis Herdiansyah; LG Saraswati Putri (Postgraduate, University of Mataram, 2023)
The ever increasing human population demands more extraction of freshwater to fulfill our basic needs. This put more pressure to the already limited water resource. The previous studies about water governance concludes that local community needs to be actively involved in an integrated water resource management (IWRM) in order to maintain sustainability. Balinese has long been known as community which always preserve water due to their belief in their local wisdom. This article aims to investigate how Balinese local wisdom play its role in the water governance. The social survey study was conducted using descriptive analysis. The data was collected in Badung District of Bali Province with purposive sampling of 100 respondents who live in Badung for the last 10 years and of 17 years old above. The result of the study shows that Balinese may not really aware about Tri Hita Karana and Sad Kertih, but they are practising its principle in their daily life. Balinese respect water as part of nature which must be preserved.